2022
DOI: 10.3390/brainsci12050518
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Macular Structural and Microvascular Changes in Thalamic Infarction Patients: A Swept-Source Optical Coherence Tomography–Angiography Study

Abstract: Background: The retina and brain share similar neuronal and microvascular features. We aimed to investigate the retinal thickness and microvasculature in patients with thalamic infarcts compared with control participants. Material and methods: Swept-source optical coherence tomography (SS-OCT) was used to image the macular thickness (retinal nerve fiber layer, RNFL; ganglion cell-inner plexiform layer, GCIP), while OCT angiography was used to image the microvasculature (superficial vascular plexus, SVP; interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 56 publications
3
16
0
Order By: Relevance
“…Our current report builds upon our previous report on retinal neurodegeneration following thalamic infarction (Ye et al, 2022) and the fundamental observations that such retrograde transsynaptic neurodegeneration after visual pathway insult follows a distinct time course and pattern (Jindahra et al, 2012;Saionz et al, 2020;Fahrenthold et al, 2021). This study showed that the LI value, which indicates the shrinkage extent of the optic tract (Bridge et al, 2011;Millington et al, 2014;Fahrenthold et al, 2021), altered distinctly compared with age-sex matched stroke-free controls.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our current report builds upon our previous report on retinal neurodegeneration following thalamic infarction (Ye et al, 2022) and the fundamental observations that such retrograde transsynaptic neurodegeneration after visual pathway insult follows a distinct time course and pattern (Jindahra et al, 2012;Saionz et al, 2020;Fahrenthold et al, 2021). This study showed that the LI value, which indicates the shrinkage extent of the optic tract (Bridge et al, 2011;Millington et al, 2014;Fahrenthold et al, 2021), altered distinctly compared with age-sex matched stroke-free controls.…”
Section: Discussionsupporting
confidence: 78%
“…Previous reports showed that transsynaptic retrograde neurodegeneration (TRD) after post-thalamic visual area (occipital lobe) stroke was high after the first few years and fairly stable over the years ( Cowey et al, 2011 ; Jindahra et al, 2012 ; Meier et al, 2015 ; Schneider et al, 2019 ). In our previous report ( Ye et al, 2022 ), thalamic infarction patients with a duration of more than 6 months also showed a thinner retinal structure compared to patients with a duration of fewer than 6 months. These findings suggest that retinal degeneration follows a clear-cut time sequence, i.e., retrograde degeneration is progressive and becomes steady over time.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Owing to its connection with the thalamus and the fact that it can be non-invasively visualized, the retina is suggested to provide important information on brain pathology [18,19]; and we assume that it could be a future target of imaging in thalamic stroke. Indeed, our previous reports have shown thalamic stroke patients have thinner retinal structures and reduced microvascular densities compared to age-and-sexmatched healthy controls [20,21]; importantly, we further showed alterations of structural changes around the optic nerve head and retina in thalamic stroke patients were related to shrinkage of the optic tract, and all these changes were correlated with visual perfomence [20].…”
Section: Introductionsupporting
confidence: 61%